Síntese, caracterização de nanopartículas de óxido de zinco e avaliação histológica de sua biocompatibilidade por meio de implantes intra-ósseos em cobaias Guinea-Pig - Oliveira, Mariana Carneiro Pereira de (2011)
Investigations about nanotechnology and the development of new materials for various applications is the fact evidenced by literature. There is, today, the lack of consensus among researchers about what the ideal material to be used as endodontic filling. Thus, the present study evaluated the synthesis, characterization and histological evaluation of zinc oxide nanocrystals through biological tests, according to criteria established by the International Dental Federation. The chemical composition and purity of the material were verified by Micro-Raman spectroscopy (Raman) and their spatial structure, phase and average of the particle size by X-ray diffraction (XRD). Ten guinea pigs (\"Guinea Pig\"), divided into experimental periods of 30 and 90 days, were used. Two intra-osseous implants were performed in each animal in the region between the mandibular symphysis, and incisors. To pack the materials tested, Teflon cups were used with their side as a control. After the experimental periods, animals were sacrificed and specimens were prepared for the routine histological examination. The nanocrystals of zinc oxide presented with a size of 21nm, hexagonal structure, not observed the presence of impurities. Tissue reaction to zinc oxide nanocrystals showed predominantly absent/mild intensity, characterized the material as biocompatible in the model test, according to the protocols of the FDI and ANSI/ADA.